Globalizing Greek Society: An Overview of Immigration to Greece - Kassimeris, Christos (Études helléniques / Hellenic Studies, 2008)
The purpose of this paper is to assess one of globalization’s immediate effects on Greek politics and society. Although Greece was, more often than not, considered as a country that had long suffered from massive trends of emigration until very recently, the postCold War era found her battling against immigration and the ensuing consequences of this phenomenon. Flows of immigration to Europe are hardly new, particularly, when considering that the European Union supports the concept of ‘movement of population,’ though not to any perverse extents. In the case of Greece, nevertheless, local authorities and the society alike have found it difficult to come to terms with the new realities dictated by globalization. It is the intention of this paper to illustrate the phenomenon of immigration in Greece immediately after the collapse of communism in Europe.